Analysis of long-term creep response characteristics of high rock slopes considering cumulative effects of earthquakes - Yu, Meilin; Deng, Hongyan (Frontiers in Earth Science, 2024)
In mountain-gorge areas, the rock creep is the critical process for high rock slopes failure. During long-term creep, slopes might encounter earthquakes and form further creep after earthquakes, which can easily lead to the slope failure. Based on a high rock slope in the Nujiang River Basin, deformation and dynamic response characteristics are analyzed by FLAC3D software, considering combined effects of multiple earthquakes and long-term creep. Results show that when the amplitude increases, the shear strength of the slope decreases and the risk of instability increases under combined actions of creep and earthquakes. Earthquakes promote the development of creep and induce the accumulation of damage on the slope surface and in the slope. The ground motion response on the slope surface is stronger than that in the slope, with the peak occurring at the top of the slope. Earthquakes have a greater impact on the middle and top of the slope surface, where cumulative damage and crack development begin. Vertical ground motion has a great effect on the dynamic response. The slope resonance leads to a larger PGA amplification factor in the vertical direction than that in the horizontal direction. Nonlinear and damping characteristics of the slope and the frequency of seismic waves cause the PGA amplification factor to decrease with increasing amplitudes. This study could promote the development of high rock slope failure mechanism and provide references for the prevention of landslides in the Nujiang River Basin.